Citizen Satisfaction with ICT Oriented Policing in Nairobi City County - Kenya - Oluoch, Awino Geoffrey; Onyango, Omboto John (Advances in Social Sciences Research Journal, 2025)
Information and Communication Technology (ICT) applications play a crucial role in decision support mechanisms within institutions, notably in law enforcement like the police. Globally, the integration of ICT has significantly enhanced the effectiveness and efficiency of policing, as seen in various countries such as the United Kingdom, USA, Sweden, and Jamaica among others. In Kenya, the National Police Service has embraced ICT systems, such as the Information Command and Control Centre and mobile applications like Hello Kenyan to improve crime prevention and service delivery. Despite these advancements, there is limited understanding of the impact of ICT adoption on citizen satisfaction with police services. Thus, this study assessed the factors mediating citizen satisfaction with ICT usage by the Kenya Police Service in Nairobi County. The study was guided by Parasuraman Zeithmal’s SERVQUAL Performance Only Model. It adopted an explanatory survey design to conduct the research in the cosmopolitan setting of Nairobi City County, Kenya. The targeted population were adult residents who had interacted with police services via ICT within the past year. Purposive sampling method was used to select 200 individuals out of which a sample of 132 was selected by simple random sampling. Data was collected by structured questionnaires and key informant interviews. Quantitative data was analysed using statistical techniques, while qualitative data underwent thematic analysis. The research established that the residents actively engaged the police on social media platforms, but usage of emergency line systems and online reporting portals was low due to accessibility challenges. The participants were satisfied with the Digital Crime Reporting System, but not response time duration. They were also positive on ICT accessibility and reliability. The study recommends the need for prompt responses to online crime reports and data security enhancements to boost citizen satisfaction.